Creating sensory smart classrooms : a practical guide for educators - Chaves, Jamie; Taylor, Ashley (Pediatric psychologist) (New York, NY : Routledge, 2021)
"Creating Sensory Smart Classrooms introduces educators to the foundations of sensory processing and offers tools to meet the wide variety of sensory needs in each classroom. This comprehensive handbook helps readers understand the neurobiology behind sensory processing and regulation issues, recognize when a student is over- or under-stimulated, and integrate different sensory inputs into the school environment. Practical and accessible chapters foster an understanding of how sensory processing influences behaviors in the classroom and how protective relationships, combined with sensory strategies, positively influence students' regulation for improved learning outcomes. Packed with useful examples, this is essential reading for teachers looking to develop the knowledge and skills they need to design sensory smart environments that support ALL learners"--
Setting the stage for learning with sensory processing -- The connection between sensory processing, regulation, and relationships -- Identifying sensory processing disorder in the school environment -- The visual system -- The auditory system -- The vestibular system -- The tactile system -- The proprioceptive system -- The gustatory, olfactory, and interoceptive systems -- Postural stability and praxis -- How sleep, diet, and screen time can influence sensory processing and regulation.
OCLC-licensed vendor bibliographic record.
Keywords: Perceptual learning; Sensory stimulation; Classroom environment; Neurobiology; EDUCATION / Special Education / General